THE INFLUENCE OF DIGITAL MARKETING, LEVEL OF EDUCATION, FINANCIAL LITERACY AND BUSINESS SUSTAINABILITY ON THE PERFORMANCE MSMEs IN KENDAL DISTRICT - Fitria Yuni Astuti; Mahfud Nugroho (Fakultas Ekonomika dan Bisnis Universitas Selamat Sri, 2023)
This study aims to determine the influence of digital marketing, level of education, financial literacy and sustainable business on the performance MSMEs in kendal district. The population of this research is MSMEs stakeholders in the Kendal Regency. The method used is simple random sampling there were as many as 63 respondents.. A Likert scale will be used to disseminate the questionnaire for this descriptive quantitative method type. The results of the study partially the digital marketing variable has no effect on the performance MSMEs, because the value of t count is smaller than t table (0.308 < 1.999) with a significance of (0.759 > 0.05).The study partially level of education variable has no effect on the performance MSMEs because the value of t count is smaller than t table (-0.838 < 1.999) with a significance of (0.405 > 0.05). According to the study's findings, the variable of financial literacy has a positive and significant impact on the performance of MSMEs because the value of t count is greater than t table (2.754 > 1.999) with a significance of (0.008 < 0.05).The study partially the business sustainability variable has a positive and significant effect on the performance MSMEs because the value of t count is greater than t table (2.967 > 1.999) with a significance of (0.004 < 0.05. The results showed that simultaneously the digital marketing, level of education, financial literacy and business sustainability variable has a significant effect on the performance MSMEs becouse the calculated Fvalue is greater than Ftable(23.195 > 2.53)with a significance of (0.000 < 0.05).Adjusted R Square value is 0.589 with means the variables of digital marketing, level of education, financial literacy and business sustainability effect the performance MSMEs in kendal district of 58.9% While 41.1% of the total was affected by factors not included in this study.